Arsen und Arsenverbindungen – Bestimmung von Arsenspezies (As(III), As(V), Monomethylarsonsäure, Dimethylarsinsäure und Arsenobetain) in Urin mittels HPLC‐ICP‐MS [Biomonitoring Methods in German language, 2018]. Issue 4 (19th October 2018) - Schramel, P.; Michalke, B.; Emons, H.; Göen, T.; Hartwig, A.; ,
Abstract: The working group "Analyses in Biological Materials" of the Permanent Senate Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area verified the presented biomonitoring method. The analytical method described hereinafter permits the simple and specific determination of the arsenic species arsenic (III) (As 3+ ), arsenic (V) (As 5+ ), monomethylarsonic acid (MMA), dimethylarsinic acid (DMA) and arsenobetaine in urine. The limits of quantitation allow the quantification of the above‐mentioned arsenic species in both occupational and environmental medicine. To this end, the arsenic species are separated by anion‐exchange high‐performance liquid chromatography (anion‐exchange HPLC) and detected by inductively coupled plasma mass spectrometry (ICP‐MS). Sample preparation is done by diluting the urine with water. Calibration is performed using either single or mixed standards of the different arsenic species or using the standard addition method. The method was extensively validated and the reliability data were confirmed by an independent laboratory, which has established and cross‐checked the whole procedure.